Elderly Well-being in Governmental and Non-Governmental Care Homes of Kathmandu (Pragyaratna प्रज्ञारत्न, 2025)
Aging leads to various changes in an individual’s well-being, necessitating extensive care. In Nepal, the transition from joint to nuclear family structures, driven by declining fertility rates and increasing migration, creates challenges for elderly care. This study investigates the impact of governmental and non-governmental of care homes on the physical and mental well-being of elderly residents. Sixty respondents aged 60 and above (37 from governmental and 23 from non-governmental care homes) were purposively selected from randomly selected One governmental and two non-governmental care homes. Selected respondents completed an interview schedule and standardized tools of Geriatric Depression Scale (GDS-15) and European Quality of Life Five Dimensions and Five Level (EQ-5D-5L), with data analyzed using Statistical Package for the Social Sciences Version 20(SPSS 20). The results show a significant relationship between the governmental and non-governmental nature of care home and the physical and mental well-being of elderly individuals. Those in governmental care homes reported better general health and lower depression levels compared to those in non-governmental care homes. Specifically, elderly residents in governmental care homes were five times more likely (aadjusted odd ratio(aOR)=5.18, 95% CI=1.12-24.00) to perceive their health positively, a statistically significant finding (p=0.036). These findings reveal clear disparities in elderly well-being between governmental and non-governmental care homes, underscoring the need to improve conditions in non-governmental settings. Enhancing health care services, providing regular psycho-social support, and ensuring consistent monitoring are essential to strengthen elderly well-being in these care homes.